Glial Cells: Role of the Immune Response in Ischemic Stroke - Xu, Shenbin; Lu, Jianan; Shao, Anwen; Zhang, John H.; Zhang, Jianmin (Frontiers in Immunology, 2020)
Ischemic stroke, which accounts for 75-80% of strokes, is a predominant cause of morbidity and mortality worldwide. Recently, post-stroke immune response becomes a new breakthrough of the treatment strategy of ischemic stroke. Glial cells, including microglia, astrocytes, oligodendrocytes, are the major components of the peri-infarction environment in the central nervous system and have been elucidated to play critical roles in post-stroke immune regulation. However, increasing evidences suggest that glial cells exert different, even contrary effect in ischemic stroke. Microglia, which survey the CNS homostasis and regulate the innate immune response, are rapidly activated following ischemic stroke. The activated microglia would release inflammatory cytokines to induce neuronal tissue injuries. On the contrary, anti-inflammatory cytokines and neurotrophic factors secreted by alternatively activated microglia are considered to be benefit for recovery following ischemic stroke. Astrocytes activation and reactive gliosis in ischemic stroke contribute to limitaion of brain injury and stabalize the CNS homeostasis. The glial scar developed by astrocytes also hinder the neuronal reconnectivity and extension. Oligodendrocytes have also been shown to be extensively involved in demyelination and remyelination after stroke. Oligodendrocyte precursor cells, which are able to differentiate into oligodendrocytes, reactived in ischemic stroke are supposed to lead to functional recovery. Here we discuss the mechanisms of post-stroke immune regulation mediated by glial cells and the interaction between glial cells and neurons. The present review, from the perspective of various glial cells, describes their possible roles at different stages of ischemic stroke and future intervention targets.